Calling cards for DNA-binding proteins - Wang, Haoyi; Johnston, Mark; Mitra, Robi David

(untitled) (Genome Research, 2007)
Identifying genomic targets of transcription factors is fundamental for understanding transcriptional regulatory networks. Current technology enables identification of all targets of a single transcription factor, but there is no realistic way to achieve the converse: identification of all proteins that bind to a promoter of interest. We have developed a method that promises to fill this void. It employs the yeast retrotransposon Ty5, whose integrase interacts with the Sir4 protein. A DNA-binding protein fused to Sir4 directs insertion of Ty5 into the genome near where it binds; the Ty5 becomes a “calling card” the DNA-binding protein leaves behind in the genome. We constructed customized calling cards for seven transcription factors of yeast by including in each Ty5 a unique DNA sequence that serves as a “molecular bar code.” Ty5 transposition was induced in a population of yeast cells, each expressing a different transcription factor–Sir4 fusion and its matched, bar-coded Ty5, and the calling cards deposited into selected regions of the genome were identified, revealing the transcription factors that visited that region of the genome. In each region we analyzed, we found calling cards for only the proteins known to bind there: In the GAL1–10 promoter we found only calling cards for Gal4; in the HIS4 promoter we found only Gcn4 calling cards; in the PHO5 promoter we found only Pho4 and Pho2 calling cards. We discuss how Ty5 calling cards might be implemented for mapping all targets of all transcription factors in a single experiment.